2011
DOI: 10.1074/jbc.m110.214056
|View full text |Cite
|
Sign up to set email alerts
|

A Central Interdomain Protein Joint in Elongation Factor G Regulates Antibiotic Sensitivity, GTP Hydrolysis, and Ribosome Translocation

Abstract: The antibiotic fusidic acid potently inhibits bacterial translation (and cellular growth) by lodging between domains I and III of elongation factor G (EF-G) and preventing release of EF-G from the ribosome. We examined the functions of key amino acid residues near the active site of EF-G that interact with fusidic acid and regulate hydrolysis of GTP. Alanine mutants of these residues spontaneously hydrolyzed GTP in solution, bypassing the normal activating role of the ribosome. A conserved phenylalanine in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
(97 reference statements)
2
12
0
Order By: Relevance
“…The folding of EF-G switch I further induces close hydrophobic packing between domains I, II and III, capped by the side chain of R59, and centered on switch II residue Phenylalanine 95 (F95) which is thought to contribute to GTPase activation (36) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The folding of EF-G switch I further induces close hydrophobic packing between domains I, II and III, capped by the side chain of R59, and centered on switch II residue Phenylalanine 95 (F95) which is thought to contribute to GTPase activation (36) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Our results clarified dose effect of each translation inhibitor. Structural analysis has revealed that fusidic acid and thiostrepton bind to specific regions of bacterial EF-G and 23S rRNA, resulting in a conformational change of EF-G that eventually perturbs its catalytic function (Gao et al 2009;Harms et al 2008;Hirose and Sugiura 1996;Rodnina et al 1999;Ticu et al 2011). Genetic analysis has also shown that the inhibitory effect of fusidic acid of EF-G can be circumvented by a single amino acid substitution in the protein (Nagaev et al 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Each of these two antibiotics greatly inhibited the incorporation of [ 14 C]Phe in the reaction (Fig. 5f, g), implying that they both target EF-G in chloroplasts as they do in bacteria (Gao et al 2009;Harms et al 2008;Rodnina et al 1999;Ticu et al 2011).…”
Section: Peptide Elongation Activity In the Chloroplast Extractmentioning
confidence: 90%
“…It has been suggested that Phe-88 plays a pivotal role in transmitting the conformational change of switch II to other domains of EF-G in a sequential manner so that EF-G acquires the conformation needed for tRNA translocation (19). This ability of Phe-88 to induce conformational change in EF-G is clearly demonstrated in the structures of mutant S. aureus EF-Gs.…”
Section: Ribosome Interactions With Ef-g and Mechanism Ofmentioning
confidence: 75%
“…The switch II region contains a set of highly conserved residues, including a Phe at its tip, which is Phe-88 in S. aureus and Phe-90 in Thermus thermophilus. This residue is thought to be important for transmitting the conformational changes of switch II between the GTP and GDP forms of EF-G (19), although direct evidence has been lacking so far. As observed in the crystal structure of T. thermophilus EF-G locked to the 70S ribosome with FA, the drug interacts directly with Phe-90 and prevents the switch II region of EF-G from going to its GDP conformation (13).…”
mentioning
confidence: 99%